Selection among alternative processes for the disposal of soapstock - Laoretani, Daniela Soledad (2017)
In this work a model is proposed to select among process alternatives that take soapstock as raw material, with the aim of maximizing economical performance, as well as disposing soapstock in an environmentally conscious way. This aim has been approached in previous literature using the traditional source-sink methodology that splits streams (with the same composition). In the present work, mass sources are connected with mass sinks through alternative “operators” (processes) whose exit streams are of different compositions. A superstructure is constructed that embeds economically feasible processes proposed in the literature, that produce intermediate goods salable to other factories or that can be recycled to the same refinery. The optimal solution for our case study was the selection of a process to obtain pre-soap to be sold to a neighbor factory that produces industrial detergents. Afterward, the price of pre-soap was halved, pretending that the closest detergent factory is located way far from the refinery. In this case, the model selects a process that separates oil to be recycled to the refining process, and FFAs to be used as fuel in the same refinery. Thus, the optimal solutions found are valid for the particular case studied, while the main contribution of this paper is the approach proposed to make a decision.